PERAN ORANG TUA DALAM PENDIDIKAN KARAKTER UNTUK MENCEGAH PERILAKU MENYIMPANG PADA REMAJA - Mulati, Yeni (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
Based on the current age composition of the population, Indonesia is predicted to get a demographic bonus from 2030 to 2040. However, the phenomenon of adolescent deviance, such as ‘klitih’, drugs abuse, cyberbullying, promiscuity, and so on, might continue to be a persistent problem in the future. Parents are one of the most important agents in nurturing positive characters. Therefore, this study tried to examine what parents can do to strengthen positive characters in teenagers and avert them from deviant behavior or juvenile delinquency. This study used literature review as the method of the research. This study found that parents’ roles should include: ensure that adolescents can go through their developmental phases well; understand adolescent psychology; and be a good role model for teenagers. Furthermore, they need to develop the 3 dimensions of character, which are moral knowing, moral feeling, and moral action. Moreover, they need to apply the appropriate parenting styles according to the needs of their teenagers. Meanwhile, to optimize children’s potential, parents are expected to implement the multiple intelligences approach in their children’s education. Cooperation with various parties, especially schools, is needed to ensure these efforts run effectively.